Antecedents of Audience Perceptions of Kompas.id’s Elementary School Cost Data Journalism - Khairunnisa Zahrah, Syifa; Merdekawati, Ika; Sri Mulyani, Henny (KOMUNIKA, 2026)
Audience perception played a crucial role in validating the significance of data journalism inthe public sphere. The features of data stories and visualisations, including data, data sources,and visualisations used, play a role in influencing their perceptions. However, this potentialremained suboptimal when audiences failed to comprehend or respond positively to datapresentations. This study aimed to examine how readers' personal characteristics influencedtheir perception and evaluation of serial data journalism coverage on elementary educationcosts at Kompas.id, particularly among members of the Investigation & Data Journalismgroup. Perception process theory and the perception of quantitative journalism were employedas the analytical framework. A descriptive quantitative method was adopted, utilizing aquestionnaire distributed via WhatsApp to 90 group members. The findings indicate thatpersonal relevance to readers' lived experiences appears to play a role in perceptual selectionwhen audiences engage with data journalism news on elementary education costs.Additionally, respondents demonstrated considerable statistical affinity, evident in theirengagement with both data sources and visualization formats. Both factors constitutedsignificant antecedents in the audience perception process of data journalism news onelementary education costs at Kompas.id.